Role of Peroxisome Proliferator-Activated Receptor Gamma (PPARγ) in Different Disease States: Recent Updates - Mal, Suvadeep; Dwivedi, Ashish R.; Kumar, Vijay; Kumar, Naveen; Kumar, Bhupinder; Kumar, Vinod (Current Medicinal Chemistry, 2021)
Peroxisome proliferator-activated receptor (PPAR), a ligand dependant transcription factor, is a member of the nuclear receptor superfamily. PPAR exists in three isoforms i.e. PPAR alpha (PPARα), PPAR beta (PPARβ), and PPAR gamma (PPARγ). These are multi-functional transcription factors and help in regulating inflammation, type 2 diabetes, lipid concentration in the body, metastasis, and tumor growth or angiogenesis. Activation of PPARγ causes inhibition of growth of cultured human breast, gastric, lung, prostate, and other cancer cells. PPARγ is mainly involved in fatty acid storage, glucose metabolism, and homeostasis and adipogenesis regulation. A large number of natural and synthetic ligands bind to PPARγ and modulate its activity. Ligands such as thiazolidinedione, troglitazone, rosiglitazone, pioglitazone effectively bind to PPARγ; however, most of these were found to display severe side effects such as hepatotoxicity, weight gain, cardiovascular complications and bladder tumor. Now the focus is shifted towards the development of dual-acting or pan PPAR ligands. The current review article describes the functions and role of PPARγ in various disease states. In addition, recently reported PPARγ ligands and pan PPAR ligands were discussed in detail. It is envisaged that the present review article may help in the development of potent PPAR ligands with no or minimal side effects.
Keywords: cancer